MODERN COMBINATION DRUGS IN THE TREATMENT OF PATIENTS WITH VARIOUS TYPES OF RHINITIS - M. A. EDZHE; A. Y. ОVCHINNIKOV (Медицинский совет, 2016)
The paper summarizes findings on the place of decongestants in current treatment approaches for various types of rhinitis, their benefits and disadvantages, as well as feasibility of combination with drugs in other pharmacological groups, in particular with the anticholinergic drug ipratropium bromide. Indications for use of xylometazoline in combination with ipratropium bromide are substantiated. The reviewed literature demonstrates that clinical use of the combination scheme with equal effectiveness in eliminating nasal congestion allows to significantly decrease rhinorrhea.